Climate Change and Migration to South Africa : Exploring the Role of Climate- and Environment-Related Adversities in Mobility Decision-Making - Wegerif, Marc (University of Pretoria, 2021)
Dissertation (MSocSci (Development Studies))--University of Pretoria, 2020.